Uptake and release of zinc by aquatic bryophytes (Fontinalis antipyretica L. ex. Hedw.) - Martins, Ramiro (2002)
The zinc uptake and posterior release by an aquatic bryophyte—Fontinalis antipyretica L. Ex Hedw.—was experimentally studied in laboratory exposing the plants to different zinc concentrations in the range, 1.0–5.0 mg l 1, for a 144 h contamination period, and then exposed to metal-free water for a 120 h decontamination period. The experiments were carried out in perfectly mixed contactors at controlled illumination, using mosses picked out in February 1997, with a background initial zinc concentration of 263mg g 1 (dry wt.). A first-order mass transfer kinetic model was fitted to the experimental data to determine the uptake and release constants, k1 and k2; the zinc concentration in mosses at the end of the uptake period, Cmu; and at the equilibrium, for the contamination and decontamination stages, Cme and Cmr; respectively. A bioconcentration factor, BCF ¼ k1=k2 (zinc concentration in the plant, dry wt./zinc concentration in the water) was determined. A biological elimination factor defined as BEF ¼ 1 Cmr=Cmu was also calculated. BCF decreases from about 4500 to 2950 as Zn concentration in water increases from 1.05 to 3.80mg l 1. BEF is approximately constant and equal to 0.80. Comparing Zn and Cu accumulation by Fontinalis antipyretica, it was concluded that the uptake rate for Zn (145 h 1) is much lower than for Cu (628 h 1) and the amount retained by the plant decreased by a factor of about seven.